2016
DOI: 10.1039/c5ce02038g
|View full text |Cite
|
Sign up to set email alerts
|

Morphological control of RGO/CdS hydrogels for energy storage

Abstract: This paper investigated the preparation of 3D RGO/CdS hydrogels by a facile hydrothermal process, the morphology control of CdS (ball-like, rod-like, needle-like) in 3D structures, and their application in electrochemical energy storage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…To address these issues various research groups have employed many strategies like self‐cross linking, fabrication of metal/metal oxide nanoparticles, supramolecular inspired synthesis of hydrogels, graphene quantum dots (GQDs) etc . Duan et al reported an asymmetric supercapacitor consisting graphene hydrogel (GH) with 3D interconnected pores as negative electrode and MnO 2 nanoplate on nickel foam as positive electrode.…”
Section: Synthetic Approaches For Selected Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…To address these issues various research groups have employed many strategies like self‐cross linking, fabrication of metal/metal oxide nanoparticles, supramolecular inspired synthesis of hydrogels, graphene quantum dots (GQDs) etc . Duan et al reported an asymmetric supercapacitor consisting graphene hydrogel (GH) with 3D interconnected pores as negative electrode and MnO 2 nanoplate on nickel foam as positive electrode.…”
Section: Synthetic Approaches For Selected Hydrogelsmentioning
confidence: 99%
“…This 3D porous composite hydrogel served as binder‐free electrode for supercapacitor . Another new 3D reduced graphene/CdS hydrogels (RGO/CdS) was prepared via facile hydrothermal process . The modified Hummers method was used for the synthesis of GO.…”
Section: Synthetic Approaches For Selected Hydrogelsmentioning
confidence: 99%
“…Also, transition metal sulfides are very good candidates as electrode materials for high energy density supercapacitor; they possess variable sulfide states which facilitate fast and successive redox reactions . Cadmium sulfide (CdS) is an example of widely studied ultracapacitive transition metal sulfide . CdS is a n‐type semiconductor with a narrow band gap (∼2.4 eV).…”
Section: Introductionmentioning
confidence: 99%
“…[17,18] Cadmium sulfide (CdS) is an example of widely studied ultracapacitive transition metal sulfide. [19][20][21][22] CdS is a n-type semiconductor with a narrow band gap (~2.4 eV). CdS nanostructures reportedly exhibits excellent morphology and high specific surface area with a particle size in the range of 5-7 nm.…”
Section: Introductionmentioning
confidence: 99%
“…The porous structure can buffer the large volume change and the agglomerations of electrode, which could be enhanced the cycling performance [16, 17]. So, one-dimensional (1D) nanofibers with porous structure have been demonstrated to be the new structure cathode for LIBs [18].…”
Section: Introductionmentioning
confidence: 99%